IMPLEMENTATION OF BRAIN GYM THERAPY IN ELDERLY WITH DEMENTIA EXPERIENCING MEMORY IMPAIRMENT AT UPTD GRIYA WREDA JAMBANGAN SURABAYA: CASE STUDY - Effendi, Rusdi (Nurse and Holistic Care, 2024)
Introduction: The aging process that occurs in the elderly can be described linearly through three stages: weakness (impairment), functional limitations, lack of ability (disabled), and obstruction (handicap). These will be experienced simultaneously with process setbacks, Good physique, mental or social. Wrong one system body which deterioration is a cognitive or intellectual system often called dementia. Efforts to prevent dementia include brain gymnastics. Objective: This research aimed to determine the application of brain gym at UPTD Griya Wreda Jambangan Surabaya. Methods: This research design uses a case study through nursing care for Mrs. M with memory problems and conducting assessments and evaluations. The data collection method is by interviewing and observing Mrs. M. Results: The results of applying brain gym for 6 x 2 weeks with a duration of 5-10 minutes showed that there was an increase in the MMSE examination score, which was obtained with a value of 21 (moderate cognitive impairment). There is an increase in the orientation section of 3 points, remembering 1 point, and language 1 point. Examination using the SPMSQ showed 3 (mild intellectual decline). Conclusions: Brain gym therapy can be used as a non-pharmacological therapy to treat memory disorders in elderly people with dementia. Health workers are expected to be able to teach and accompany the elderly in implementing brain gymnastics as an effort to maintain the cognitive function of the elderly.